Flood Risk and Resilience - Fu, Guangtao; Casado, Monica Rivas; Meng, Fanlin; Kalawsky, Roy (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Flooding is widely recognized as a global threat, due to the extent and magnitude of damage it causes around the world each year. Reducing flood risk and improving flood resilience are two closely related aspects of flood management. This book presents the latest advances in flood risk and resilience management on the following themes: hazard and risk analysis, flood behaviour analysis, assessment frameworks and metrics and intervention strategies. It can help the reader to understand the current challenges in flood management and the development of sustainable flood management interventions to reduce the social, economic and environmental consequences from flooding.